Enhancement of Antibiotic Activity and Reversal of Resistance in Clinically Isolated Methicillin-Resistant Staphylococcus aureus by Trachyspermum ammi Essential Oil - Mahdi Vazirian; Khadijeh Hamidian; Mehrzad Noorollah; Azadeh Manayi; Nasrin Samadi* (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Methicillin-resistant Staphylococcus aureus (MRSA) has resulted in a worldwide threat due to the virulence and broad distribution in the hospital and community. Novel antibiotics are required to combat the emergence of multidrug-resistant bacteria such as MRSA. In the present study, the antibacterial activity of Trachyspermum ammi essential oil alone and in combination with fifteen antibiotics of different classes against a standard and five clinical strains of MRSAs was investigated. Methods: Chemical composition of the essential oil was investigated by using gas chromatography-mass spectrometry (GC-MS). The possible synergistic interaction of several antibiotics in combination with essential oil was screened by disc diffusion method. Interaction of the essential oil and the candidate antibiotic was investigated by checkerboard assay. Results: The essential oil was rich in thymol (74.2%), p-cymene (16%), and γ-terpinene (7.1%). Combination of sub-inhibitory concentrations of essential oil with vancomycin or gentamicin increased their inhibition zones against MRSA ATCC 33591 and clinically isolated MRSAs. All of the clinically isolated MRSAs were resistant to gentamicin, while combination of gentamicin with the essential oil caused augmentation of the antibacterial activity and 4 to 520-fold decrease in gentamicin minimum inhibitory concentrations was observed against different MRSA strains with fractional inhibitory concentration indices ranging from 0.50 to 0.75. Combination of essential oil with ciprofloxacin or imipenem increased the inhibition zones against some clinically isolated MRSAs. Conclusion: Combination of sub-inhibitory concentrations of T. ammi essential oil and gentamicin could be considered as a new choice for treatment of infectious diseases caused by MRSA strains.